Analysis of Water Quality Status of Karang Mumus River Segment Gunung Lingai dan Gelatik Samarinda - Pramaningsih, Vita; Janarika, Angel; Daramusseng, Andi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Water is a basic need for plants, animals, and humans. All daily activities require water, both as drinking water and as a fulfillment of needs in daily activities. The main problem is that surface water is often polluted, reducing water quality. The research was conducted using descriptive research methods with a quantitative approach. The results of the measurements of the eight water parameters of the Karang Mumus River in the Gunung Lingai Segment are TSS 39 mg/L, BOD 1.575 mg/L, COD 38.657, nitrate 0.137 mg/L, phosphate 0.085 mg/L, DO 2.925, fecal coli 81600/100 ml water, and pH 7.615. The measurement results of the Karang Mumus river water parameters in the Gelatik Segment are TSS 32.2 mg/L, BOD 1.75 mg/L, COD 21.701, nitrate 0.129 mg/L, phosphate 0.077 mg/L, DO 3.25, fecal coli 231200/100 ml water, and pH 6.67. The research results on the Karang Mumus River, Segments of Gunung Lingai and Gelatik, showed the same results. Calculation of the water quality status of the Karang Mumus River in the Gunung Lingai segment shows a value of 7.577. This value is included in the category of moderate contamination. Calculation of the water quality status of the Karang Mumus River in the Gelatik Segment is also included in the moderately polluted category with a pollution index value of 9.173.